The Correlation of work stress on Employee turnover intention : Job Satisfaction as mediating variable - Setyaningsih, Meylina; Bahiroh, Eloh; Khaerunnisa, Enis (PT Larva Wijaya Penerbit, 2024)
This study aims to determine the role of Job Satisfaction in mediating the relationship between Job Stress and Turnover Intention at PT Gilang Lemindo Sejahtera Tangerang. The research method used is quantitative with a descriptive approach. This research collects data based on questionnaires and literature studies. The population and samples used in this study were all employees at PT Gilang Lemindo Sejahtera, totaling 78 respondents. The data analysis method used is Structural Equation Modeling (SEM) with the SmartPLS 4.1.0.0 analysis tool. The results of this study indicate that: (1) Job Stress has a positive and significant effect on Turnover Intention. (2) Job Stress has a negative and significant effect on Job Satisfaction. (3) Job Satisfaction has a negative and significant effect on Turnover Intention. (4) Job Satisfaction is able to mediate the effect of Job Stress on Turnover Intention